2014
DOI: 10.1002/cpdd.132
|View full text |Cite
|
Sign up to set email alerts
|

Impact on abiraterone pharmacokinetics and safety: Open‐label drug–drug interaction studies with ketoconazole and rifampicin

Abstract: We evaluated the impact of a strong CYP3A4 inhibitor, ketoconazole, and a strong inducer, rifampicin, on the pharmacokinetic (PK) exposure of abiraterone in two studies in healthy men. All subjects received 1,000 mg of abiraterone acetate on Days 1 and 14. Study A subjects (n = 20) received 400 mg ketoconazole on Days 11-16. Study B subjects (n = 19) received 600 mg rifampicin on Days 8-13. Serial PK sampling was done on Days 1 and 14. Study A: When given with ketoconazole, abiraterone exposure increased by 9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…Abiraterone acetate and abiraterone sulfate were predicted to have K i values (inhibition constant = 0.5 Â IC 50 ) below 1 mM, which suggest high in vitro potency to cause in vivo drug interaction of at least two-fold (Obach et al, 2005). In a previous study, C max of abiraterone, abiraterone sulfate, and N-oxide abiraterone sulfate were reported to be approximately 0.37 mM, 25 mM, and 9.2 mM, respectively, after a single-dose administration of 1000 mg of abiraterone acetate to healthy volunteers (Bernard et al, 2015). The calculated R values (= 1 + [I] /K i ]) were greater than 1.1 for abiraterone and its metabolites, thus pointing toward the need for a clinical study to assess the interaction further.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Abiraterone acetate and abiraterone sulfate were predicted to have K i values (inhibition constant = 0.5 Â IC 50 ) below 1 mM, which suggest high in vitro potency to cause in vivo drug interaction of at least two-fold (Obach et al, 2005). In a previous study, C max of abiraterone, abiraterone sulfate, and N-oxide abiraterone sulfate were reported to be approximately 0.37 mM, 25 mM, and 9.2 mM, respectively, after a single-dose administration of 1000 mg of abiraterone acetate to healthy volunteers (Bernard et al, 2015). The calculated R values (= 1 + [I] /K i ]) were greater than 1.1 for abiraterone and its metabolites, thus pointing toward the need for a clinical study to assess the interaction further.…”
Section: Discussionmentioning
confidence: 88%
“…The small decreases in metabolite concentrations suggest that their formation was minimally affected by CYP2C8 inhibition caused by abiraterone. Although the enzymes involved in the metabolism of M-IV and M-III have not been identified, it has been reported that clearance of M-IV and M-III is inducible by rifampicin (Bernard et al, 2015;Jaakkola et al, 2006a), suggesting that CYP450s regulated by the pregnane X receptor gene may play a role (e.g., CYP3A4, CYP2C family). Considering the overall effect based on exposures to the total active compounds (sum of pioglitazone, M-III, and M-IV), it is probable that the net effect of abiraterone is a slight increase in the efficacy of pioglitazone by approximately 26% only.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of cabozantinib are readily altered by agents that significantly inhibit or induce CYP3A4 activity . Systemic exposure to abiraterone was decreased by 55% when given to subjects that had been pretreated with the strong CYP3A4 inducer rifampin but not significantly affected when coadministered with the strong CYP3A4 inhibitor ketoconazole . The plasma pharmacokinetics of erlotinib, an approved anticancer drug for which CYP3A4 metabolism represents a prominent route of its elimination, was not affected by the coadministration of cabozantinib in a phase I study in patients with solid tumors .…”
Section: Discussionmentioning
confidence: 99%
“…The AA tablets should be swallowed whole with water and should not be crushed or chewed [7]. Several studies have investigated the effect of food on AA absorption and bioavailability [8][9][10][11][12] and established that consumption of a high-fat meal before administration of the originator AA (OAA) formulation markedly increases abiraterone absorption [9,10,12].…”
Section: Introductionmentioning
confidence: 99%